Electronic word-of-mouth and tourist satisfaction in rural tourism in schist villages - Santos, M.; Rita, P.; Moro, S.; Alturas, B. (Exploring niche tourism business models, marketing, and consumer experience, 2023)
Consumers' decision-making processes and the way they purchase their products and services have been evolving over the years due to the influence of information technologies. Tourists are increasingly making their decisions based on online reviews made by other users, which contain descriptive comments and/or a rating system, leveraging electronic word-of-mouth (eWOM). This study aims to understand the variation of the eWOM in rural tourism as well as unveil the main characteristics that influence the satisfaction and the interest of the consumers. To that end, the content of the comments and quantitative classification of Portuguese schist villages' lodgings on the platforms of TripAdvisor and Facebook were studied using both sentiment polarity and frequency analysis. The results show that eWOM has increased in rural tourism and that the satisfaction of tourists are more influenced by the friendliness of the hosts, the variety and good breakfast or Portuguese cuisine, and the service provided.